Thyroid cancer in Brazil: a descriptive study of cases reported between 2013-2020 (Research, Society and Development, 2023)
The objective was to analyze the reported cases of thyroid cancer in Brazil, associating the variables: age group, gender, federative unit of diagnosis, year of diagnosis, detailed diagnosis, and therapeutic modality. Thus, was conducted a descriptive epidemiological study of quantitative character, using data available in the official notification bank of the Ministry of Health/Brazil, DATASUS. And because they are secondary data and in the public domain, it was not necessary to submit this study to the Research Ethics Committee. According to the period investigated, there was a total of 19.122 cases of thyroid cancer reported, 3.074 in men, equivalent to 16.08%, and 16.048 in women, with a percentage of 83.92%. Furthermore, it is possible to verify that cases of thyroid cancer in men and women had a significant increase in the period from 2018 to 2021, if compared to previous years. However, the cases in the female gender obtained an increase from 2017 to 2018 of about 39 times. It is concluded that the incidence and prevalence of thyroid cancer have increased in recent years, especially in females, and the age group 50 to 54 years was the most prevalent, obtaining 944 cases, being the highest rate in the period analyzed and among the other age groups.